Curcuma longa on the Metabolic Profile and Atherogenic Index of Rats Fed with a Hyper Caloric Diet - Elen Landgraf Guiguer,; Sandra Maria Barbalho,; Adriano Cressoni Araújo,; Maricelma da Silva Soares Souza,; Patrícia Cincotto dos Santos Bueno,; Claudemir Gregório Mendes,; Sara da Silva Barbosa,; Eliane Paschoal da Silveira ,; Daniel Pereira Coqueiro, (Journal of Pharmacy and Nutrition Sciences, 2015)
The chronic diseases such as diabetes mellitus, metabolic syndrome and cardiovascular diseases have reached epidemic proportions in developed and developing countries. The high costs of the allopathic medicines represent a growing demand for non-allopathic alternatives. Curcuma longa is usually used as a spice in curries and as a dietary pigment and is considered a medicinal plant due important properties, with anti-inflammatory, anti-oxidant, anti-bacterial and anti-tumor action.The aim of this work was to evaluate the effects of Curcuma longa on the metabolic profile of Wistar rats treated with hyper caloric diet. Forty eight male rats were divided randomly into 4 groups (n=12) and treated for 40 days: G1 that received water (Control Group); G2 that received condensed milk solution ad libitum; G3 that received C. longa by gavage route and G4 that received condensed milk solution ad libitum and C. longa by gavage route. No significant differences for body weight and cholesterol were observed among the groups. Visceral fat, triglycerides and glycaemia were higher in the groups treated with condensed milk but did not differ when comparing G1 with G3 and G2 with G4. Analyzing our results it is possible to say that C. longa may not be efficient to promote benefits in lipid and glycemic profile as well as in the body weight and visceral fat of animals treated with hyper caloric diet.